ANALYSIS OF THE CHALLENGES AND STRATEGIES FOR IMPLEMENTING INTERACTIVE TECHNOLOGIES IN HIGHER EDUCATION (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.